2014
DOI: 10.5603/fm.2014.0069
|View full text |Cite
|
Sign up to set email alerts
|

Sex determination based on the analysis of a contemporary Polish population’s palatine bones: a computed tomography study of 1,200 patients

Abstract: (Folia Morphol 2014; 73, 4: 462-468)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
4
18
3
Order By: Relevance
“…Sexual dimorphism of the greater palatine canal has been previously reported by Sheikhi et al ( 2013 ), and we agree that the craniofacial complex is highly variable in both size and shape by sex and that the zygomatic curve and skull size are generally larger in males than in females (Bigoni et al 2010 ). In a previous study (Tomaszewska et al 2014b ) we found that the length of the GPC, among other variables, can be successfully used to distinguish between sexes, with an overall accuracy of >78 %. In the present study we found a number of rather discrete side-related differences in both males (GPF lateral-medial dimension) and females (GPC length).…”
Section: Discussionmentioning
confidence: 80%
“…Sexual dimorphism of the greater palatine canal has been previously reported by Sheikhi et al ( 2013 ), and we agree that the craniofacial complex is highly variable in both size and shape by sex and that the zygomatic curve and skull size are generally larger in males than in females (Bigoni et al 2010 ). In a previous study (Tomaszewska et al 2014b ) we found that the length of the GPC, among other variables, can be successfully used to distinguish between sexes, with an overall accuracy of >78 %. In the present study we found a number of rather discrete side-related differences in both males (GPF lateral-medial dimension) and females (GPC length).…”
Section: Discussionmentioning
confidence: 80%
“…The first equation was based on orale-spina nasalis posterior distance and had a sexing accuracy of 68.35%. The second equation was based on right greater palatine canal depth, orale-spina nasalis posterior distance and the anterior width of palatal arch and had a sexing accuracy of 78.37% [ 17 ]. The orale-spina nasalis posterior distance measured in this study is marginally longer than the incisive fossa to posterior nasal spine distance measured in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The maxilloalveolar length was extremely significant with a P -value of 0.001 [ 18 ]. The orale-spina nasalis posterior distance in CT scans was also extremely significant with a P -value less than 0.001 [ 17 ]. In our present study all the three sagittal dimensions were extremely significant; the incisive fossa to posterior nasal spine distance with P -value less than 0.001, the palatine process of maxilla length with P -value of 0.004, and the horizontal plate palatine bone length with P -value less than 0.001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Both palatine nerves -the greater and the lesser palatine nerve -originate from the sphenopalatine ganglion. The greater palatine nerve descends through the greater palatine canal (mean canal length 31 mm, range 15-44 mm) [35,36], and the greater palatine foramen to run anteriorly in a groove on the inferior surface of the hard palate. It innervates the hard palate and the palatal gingiva.…”
Section: Anterior Superior Alveolar Nervementioning
confidence: 99%